2022
DOI: 10.1111/ina.12981
|View full text |Cite
|
Sign up to set email alerts
|

Global magnitude and long‐term trend of ischemic heart disease burden attributed to household air pollution from solid fuels in 204 countries and territories, 1990–2019

Abstract: Understanding the spatiotemporal variation in the household air pollution from solid fuels (HAP)-related ischemic heart disease (IHD) burden on a global scale from 1990 to 2019 is essential to reduce IHD burden, as well as control HAP exposure. Based on the Global Burden of Disease Study 2019, the numbers and age-standardized rates of IHD mortality and disability-adjusted life years (DALYs) (ASMR and ASDR) attributed to HAP were analyzed by sex and age at global, regional, and national levels. The estimated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…Information such as the socio-demographic index (SDI) and corresponding age-standardized rates was also downloaded from this website for the following correlation analysis. Based on the SDI, 204 countries and territories were divided into five super regions, namely, low, low-middle, middle, middle, and high SDI ( 24 , 25 ). According to GBD 2019, SDI is an indicator of a country's level of health development, based on fertility rates for women under 25 and total fertility rates for men, education attainment among those 15 years of age and older, and 10-year lag-distributed average individual incomes ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Information such as the socio-demographic index (SDI) and corresponding age-standardized rates was also downloaded from this website for the following correlation analysis. Based on the SDI, 204 countries and territories were divided into five super regions, namely, low, low-middle, middle, middle, and high SDI ( 24 , 25 ). According to GBD 2019, SDI is an indicator of a country's level of health development, based on fertility rates for women under 25 and total fertility rates for men, education attainment among those 15 years of age and older, and 10-year lag-distributed average individual incomes ( 26 ).…”
Section: Methodsmentioning
confidence: 99%
“…The regression model was used to fit the age-standardized rate (ASR), that is, ln (ASR) = α + βX + ε, where y stands for the burden rate and x for the calendar year. EAPC was calculated by 100 × [exp (β)−1], and its 95% confidence interval (CI) could also be calculated from the model ( 24 , 25 , 30 ). With the EAPC value and its 95% CI above zero, the corresponding age-standardized rate (ASR) was in an upward trend and vice versa ( 31 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Household air pollution from solid fuel mainly refers to exposure to particulate matter with an aerodynamic diameter of less than 2.5 micrometer (PM 2.5 ) via the use of polluting fuel (wood, coal, kerosene, charcoal, agricultural residues, or animal dung) for household heating or cooking. It has been listed as an important risk factor for cardiovascular and metabolic diseases [10][11][12]. For example, Yu et al reported [13] that solid fuel use was associated with higher risks of cardiovascular and all-cause mortality in rural China.…”
Section: Introductionmentioning
confidence: 99%
“…Despite significant advances in surgery and drug therapy in recent years, ischemic heart disease remains a leading cause of death worldwide (1)(2)(3). A reduction in myocardial oxygen supply due to thrombosis caused by coronary atherosclerotic plaque leads to cardiac tissue damage and subsequent biochemical and metabolic changes that ultimately lead to myocardial cell death (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%